IMPROVING STUDENTS' VOCABULARY MASTERY USING LISTENING AND DRILLING METHOD AT THE FIRST YEAR IN CLASS VII.A STUDENTS OF SMP NEGERI 1 BUA KABUPATEN LUWU (A Classroom Action Research) - Daming, Srinanengsi; Haerah Syam, Ummu; G, Wahidah; Rosmiati, Rosmiati; Yanti, Yuliana Agustina (La Ogi : English Language Journal, 2024)
This research aimed to find out the improvement of the students' vocabulary in term of Adjective and Verbs through Listening and Drilling method at The First Year In Class VII.A Students of SMP Negeri 1 Bua Kabupaten Luwu. The method of this research was Classroom Action Research that consisted of two cycles. One cycle consisted of four meetings, it means that there were eight meetings for two cycles. This classroom action research was done at The First Year In Class VII.A students of SMP Negeri 1 Bua Kabupaten Luwu, the sample of the research consisted of 28 students. The instrument were vocabulary test, it was used to measure the students achievement in using Adjective and Verb. The findings of the research were the students' vocabulary achievement in cycle 1, the data obtain from the test were analyzed into percentages. Mean score of Adjective in cycle I was 54.78 and verb was 57.23, meanwhile mean score of Adjective in cycle Il were 75.86 and verb 71.76. The students' participation in learing vocabulary through listening and drilling method in the first meeting of cycle 1 was 32.89% then it became 63.15% in fourth meeting of cycle II. The result of data analysis showed that there was a significant difference between cycle I and cycle Il. Based on findings, it was concluded that Teaching Vocabulary through Listening and Drilling method was able to improve the students' achievement in using Adjectives and Verbs.